Nanowire morphology and particle phase control by tuning the In concentration of the foreign metal nanoparticle. (4th December 2018) - Hallberg, Robert T; Messing, Maria E; Dick, Kimberly A
Abstract: Controllable particle assisted growth (PAG) of III–V nanowires is today almost exclusively done with Au, Ga or In nanoparticles, whereas other metals often yield nanowires with uncontrolled growth directions. To improve the control of the initial growth direction in PAG, independent of choice of metal, we propose to initiate nanowire growth from a group-III-rich foreign metal particle. For III–V nanowire growth, the group III concentration of the particle can be made to increase or decrease with the relative supply of group III and group V material, which can be used to promote the liquid phase that is necessary for vapor–liquid–solid growth. In this paper, 30 nm Pd nanoparticles are used to develop growth conditions for In-rich PAG of InAs nanowires. The particle size evolution for different growth times and V/III ratios is correlated with changes in nanowire density and morphology. In addition, we demonstrate In-rich Co, Pd, Pt and Rh nanoparticles and optimized In-rich PAG from Au and Pd seeds. The Au and Pd seeded nanowires are remarkably similar and by tuning the particle composition we trigger a morphological change. The vertical nanowire morphology is associated with In-rich nanoparticles that contain a liquid phase. The curly nanowire morphology, with random growth directions have an In concentration less than or equal to that of the most In rich compound of the seed metal–In system.